Monday

April 21, 2014

April 21, 2014

Posted by **Brandon** on Tuesday, November 24, 2009 at 11:06am.

- Math -
**MathMate**, Tuesday, November 24, 2009 at 3:44pmLet x=π/4, y=π/4,

cos(x+y)

=cos(π/4+π/4)

=cos(π/2)

=0

cos(x)+cos(y)

=cos(π/4)+cos(π/4)

=√2/2+√2/2

=√2

Since √2 ≠ 0,

cos(x+y) ≠ cosx +cosy

**Related Questions**

Math - Use a counter example to show that cos(x+y)= cosx +cosy is not an ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

Trigonometry - Write equivalent equations in the form of inverse functions for a...

math - sinx+ siny/ (cosx+cosy)= tan 1/2 (x+y) prove this identity

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

Math help again - cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...